DESAIN PROMOSI RUMAH KOPI NUNOS MELALUI MEDIA WEBSITE - YOLANDA RAHMI ARICI, Drs. Ariusmedi, M.Sn, Ishakawi, S.Pd, M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Rumah Kopi Nunos is a well-designed coffee shop located on kis mangunsakoro street number a- 13, Padang. It was opened to public since nov 11th 2011. There were many promotions done topopularize this coffee shop but it seemed unsuccessful because the promotions were just by mouth to mouth promo and by social media promo such as facebook and twitter. From this background, it can be seen that Rumah Kopi Nunos needs a new way in promoting their coffee shop; that ispromoting it by using website. Website is a media of internet which can be built by company, organization or individuals and can be visited onlineby many internet users. Website is chosen as the main media used for promotion because nowadays technology and info can be accessed easily.Kata Kunci : Desain, Website, promosi, Rumah Kopi Nunos